Genes candidatos para características de produção de carne em famílias de referência da raça Nelore - Tizioto, Polyana Cristine (Universidade Federal de São Carlos, 2010)
To remain competitive in the market of meat production, it is crucial that the Brazilian producer is aware of the criteria used by consumers for local and international markets. One factor that determines the beef quality is genetics, so it is necessary to conduct studies in Brazil to understand the genetic variation of carcass and meat quality traits in order to outline plans to improve such attributes. Backfat thickness (BFT) and ribeye area (RAE) are characteristics of late measurements, so the investigation of molecular markers associated with these characteristics can help in their inclusion in breeding programs. In cattle, some polymorphisms have been related to characteristics of meat production. Thus, this work aimed to assess the presence of polymorphisms in candidate genes PPARGC1A (peroxisome proliferative active recptor gamma coactivator 1A), FABP4 (fatty acid binding protein 4), DDEF1 (development and differentiation enhancing factor 1), Leptin, PSMC1 (proteasome 26S subunit, ATPase, 1) and IGF-1 (insulin-like growth factors) and associate them with production traits in reference families of Nellore breed. We used 280 steers descendants of 20 sires, that were chosen to represent the variability in Nellore. The sires were genotyped for all markers to investigate their allelic distribution within the race. The SNPs of the leptin and PSMC1 genes showed no variability in the bulls, so these were not genotyped in the progeny. The other markers were genotyped for the whole population. The investigation of the effects of markers on the characteristics was performed using a mixed model, including fixed and random effects, using the restricted maximum likelihood method. There was a significant association (P<0,05) between FABP4 and BFT and a suggestive association (P<0,10) between fat gain in the feedlot and these marker. Significant association was found between RAE, weaning weight (WW) and yearling weight (YW) and the DDEF1 gene and a suggestive association between the IGF-1 gene and YW in this sample of Nellore cattle.
Keywords: Genética molecular; Polimorfismo; Zebu; Nelore; Carne bovina; Beef; Production traits; Polymorphism; Nellore; Bos indicus; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL